Relationship Between High Blood Pressure, Atrial Cardiopathy, and Mortality in the General Population. (21st July 2022) - Imtiaz Ahmad, Muhammad; Mendys, Phil M; Kelly, Scott P; Chen, Lin Y; Soliman, Elsayed Z
Abstract: BACKGROUND: Atrial cardiopathy is associated with an increased risk of mortality. However, it is unclear whether this association is modified by hypertension, a risk factor for both atrial cardiopathy and mortality. Methods: This analysis included 8, 023 participants from the Third National Health and Nutrition Examination Survey. Electrocardiographic deep terminal negativity of P-wave in V1 ≥100 µV defined atrial cardiopathy. National Death Index was used to identify the date and cause of death. Cox proportional hazard analysis was used to examine the association of atrial cardiopathy with mortality among participants stratified by hypertension status. RESULTS: In total 2.7% of the participants had atrial cardiopathy. Over a median follow-up of 14 years, 2, 922 all-cause deaths occurred, of which 1, 058 were CVD. All-cause death rates were almost double among participants with concomitant atrial cardiopathy and elevated blood pressure (BP) (120–129/<80), stage 1 (130–139/80–89), or stage 2 hypertension (≥140/≥90) compared to their counterparts in the same hypertension stages without atrial cardiopathy (47.8, 61.3, and 80.2 vs. 23, 24.7, and 44.8 per 1, 000 person-years (PY), respectively). In multivariable-adjusted models, a stronger association between atrial cardiopathy and all-cause mortality was observed in the presence compared to the absence of hypertension (HR (95% CI): 1.59 (1.25–2.01) vs. 0.67 (0.41–1.10), respectively, interaction P -value = 0.009). Similarly, an association between atrial cardiopathy and cardiovascular disease (CVD) mortality was observed in the presence compared to the absence of hypertension (HR (95% CI): 1.64 (1.08–2.47) vs. 0.63 (0.20–2.00), respectively, interaction P -value = 0.20). CONCLUSIONS: Concomitant presence of high BP and atrial cardiopathy carries a higher risk of mortality, and the risk increases with higher BP levels. Graphical Abstract: